Interferon-inhibited human osteosarcoma xenografts induce host bone in nude mice. - Forster, S; Triffitt, J; Bauer, H; Brosjö, O; Nilsson, O; Smith, R; Sykes, B (1988)
The growth of human osteosarcoma xenografts in nude mice can be inhibited by human interferon-alpha (IFN-alpha). Histologic examination of growth-inhibited tumors has revealed mineralization and partial replacement of the tumor by normal bone tissue. We have investigated whether the normal bone tissue was formed by differentiated tumor cells or by induction of host stroma to differentiate into bone tissue. Employing antibodies to both murine and human type I collagen, it was found that the normal bone produced in IFN-inhibited osteosarcomas was host derived. These results suggest that IFN induced the osteosarcoma cells to produce a bone-inductive agent that interacts with the host cells, and leads to the formation of mature normal bone tissue in a heterotopic site.